Incidence and risk factors of second primary cancer after the initial primary human papillomavirus related neoplasms. Issue 3 (3rd December 2020) - Shen, Jiayi; Zhou, Huaqiang; Liu, Jiaqing; Zhang, Zhonghan; Fang, Wenfeng; Yang, Yunpeng; Hong, Shaodong; Xian, Wei; Ma, Yuxiang; Zhou, Ting; Zhang, Yaxiong; Zhao, Hongyun; et al.
Abstract: Comprehensive studies in second primary cancer (SPC) after the initial primary human papillomavirus (HPV)‐related cancer still remain warranted. We aimed to analyze the incidence and risk factors of SPC after HPV‐related cancer. We identified 86 790 patients diagnosed with initial primary HPV‐related cancer between 1973 and 2010 in the SEER database. Standardized incidence ratio (SIR) and cumulative incidence were calculated to assess the risk of SPC after HPV‐related cancer. The SIR of SPC after HPV‐related cancer was 1.60 (95% confidence interval [CI], 1.55‐1.65) for male and 1.25 (95% CI, 1.22‐1.28) for female. SIR of second primary HPV‐related cancer (7.39 [95% CI, 6.26‐8.68] male and 4.35 [95% CI, 4.04‐4.67] female) was significantly higher than that of HPV‐unrelated cancer (1.54 [95% CI, 1.49‐1.60] male and 1.16 [95% CI, 1.13‐1.19] female). The 5‐year cumulative incidence of SPC was 7.22% (95% CI, 6.89‐7.55%) for male and 3.72% (95% CI, 3.58‐3.88%) for female. Risk factors for SPC included being married and having initial primary cancer (IPC) diagnosed at earlier stage for both genders, and IPC diagnosed at older age as well as surgery performed for female. Patients diagnosed with HPV‐related cancer are more likely to develop another primary cancer, compared with the age‐specific reference population. Abstract : Our study performed a systematic estimation of the incidence of second primary cancer in HPV‐related cancer patients. This figure displayed the distribution of second primary cancer sites after the specific initial primary HPV‐related cancer. The result may provide some accordance for the surveillance of second primary cancer after initial primary HPV‐related cancer.